Possibilities and limitations of school notebooks as curricular material. A study on the subject - Badanelli Rubio, Ana María; Mahamud Angulo, Kira (Avances en Supervisión Educativa, 2007)
School notebooks emerge as rich, varied, valid and necessary  documentary sources of information to widen and complete studies materialized in three concomitant fields of investigation, which are: History of Childhood, History of Education ( and some of its subdued subjects, such as History of School, History of Overall Study, Educational Practice and Educational Culture) and Culture in Written Form.Despite being a documentary proof which is complex from every point of view, the knowledge that school notebooks provide is unique, due to the students' authorship (and teachers' in certain cases), literal information and, consequently, their condition of genuine school-born product.